Synthetic ligands for PreQ1 riboswitches provide structural and mechanistic insights into targeting RNA tertiary structure - Colleen M. Connelly (Nature Portfolio, 2019)
RNA sensors—Riboswitches—respond to the binding of small molecules ligands through structure modification. Here the authors identify synthetic small molecules that bind and regulate the activity of PreQ1 Riboswitches despite having no obvious chemical similarity to the cognate ligand.